Tipikal Gender dalam Mengkomunikasikan Penyelesaian Masalah Matematika Sekolah Menengah Pertama - N. Nuralam; Muhammad Yani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2019)
[Title: Gender Typical in Communicating Middle School Mathematical Problem Solving]. The emphasis of mathematics learning, especially students' communication skills, needs to be considered from gender equality in solving mathematical problems. This study aims to describe: 1) the potential Mathematical Communication Skills (MCS) of students based on gender; 2) gender equality in communicating mathematical problem solving, and 3) the suitability of the form of the model or the applied form to develop students' MCS based on gender at school. This research is descriptive qualitative research conducted on all junior high school students in Langsa with a purposive sampling technique of 283 students. The data were collected through MCS and questionnaire tests which were analyzed descriptively using the concept of Miles and Huberman. The results showed that: 1) MCS of female students were better than male students in solving mathematical problems; 2) MCS of male students are better in suburban schools and female students are better in downtown schools, and 3) learning implementation plans are still limited in emphasizing MCS and learning tends to be cooperative and individual. It is recommended that learning plans refer to developing MCS that pay attention to students' gender equality in order to optimize mathematical problem-solving.